Francisco de Terrazas, poeta toscano, latino y castellano - Bustos Táuler, Álvaro (Dicenda. Estudios de lengua y literatura españolas, 2003)
Francisco de Terrazas is considered the first petrarquist poet of New Spain. The early date of his death (1580) did not impede a madure assimilation of the petrarquist imagery, through the so-called seville school. These pages suggest Terrazas relationship with the neolatin poetry of the Licenciado Francisco Pacheco as well as with the amorous poetry of Juan de la Cueva, whom he could have known in New Spain.